Exploring delusional parasitosis – a case series of three patients - Pathak, Abhishek; Singh, Manish; Rana, Yogi; Yadav, Vishesh; Singh, Rahul (Asian Journal of Medical Sciences, 2024)
Delusional parasitosis is a psychiatric condition where individuals believe they are infested with parasites despite lacking medical evidence. This often leads to underestimation within psychiatric settings. Three patients with delusional parasitosis, aged above and below 50, presented with symptoms lasting from 1 to 6 months. Two had consulted specialists before, and one had primary delusional parasitosis while two had secondary due to schizophrenia and depression. Tablet Olanzapine showed partial response in one patient before admission. Tablet Risperidone resulted in complete symptom resolution within 10 days in two patients and within 1 month in one patient. Randomized controlled trials on antipsychotics for delusional parasitosis treatment are lacking. Further research is needed to assess treatment recommendations. Psychiatrists should report cases to provide clinical evidence supporting treatment decisions.